(untitled) (Jurnal Geomine, 2019)
Natural disasters are events that need to be carried out more in-depth research to minimize losses caused by disasters. This study aims to determine the extent of landslide-prone areas, the level of landslide disaster areas and foktor that can cause landslides. The research method is carried out using a geographic information system (GIS) application which consists of rainfall data, land use, slope, soil type, lithology of rock, landform and geological structure. The data is then scored to obtain an area of landslide hazard level. The results obtained four zones of landslide hazard level, namely a low landslide hazard zone with an area of 3.656 Ha, a moderate landslide hazard zone with an area of 22.628 Ha, a high landslide hazard zone with lus 42.063 Ha and a landslide hazard zone of 331 Ha. The results obtained identified that the potential of landslide hazard camels was caused by high rainfall of 3826 mm / year. The wide slope area of 40% to 100% is also a factor that causes potential landslides.